Public Consultation Regulations on Land Acquisition for Toll Roads for Public Interests in the Perspective of Law Number 2 of 2012 - Senia Dwi Astuti; Diyan Isnaeni (Journal of Law, Politic and Humanities, 2024)
Public Consultation serves as a mechanism to gather the thoughts, ambitions, and concerns of the community pertaining to land acquisition projects. In the realm of land purchase for public interest, Public Consultation is not merely a formality; it is a crucial step for enhancing decision-making, fostering public engagement, and establishing a robust foundation for sustainable development. The concept of public interest in land acquisition for toll roads, as delineated in Law No. 2 of 2012 regarding Land Acquisition for Development in the Public Interest, indicates that such acquisition is categorized under Article 10, letter b, which classifies toll roads as a form of land acquisition serving the public interest. This is substantiated by the Constitutional Court Decision; furthermore, property acquisition for toll highways satisfies the criteria for the concept of interest outlined in Article 6, specifically for the interests of the nation, state, and society, regardless of whether it is publicly communicated to the community.